The impact of internet access at home and/or school on students' academic performance in urban areas in Brazil. (2018) - Badasyan, Narine; Silva, Simone
Using the propensity scores matching methodology, the paper assesses the impact of internet access at school and/or at home on standardised Portuguese and Mathematics tests of 9th graders in urban public schools in Brazil for years 2007 and 2009. The results suggest that internet access at home considerably improves Portuguese and mathematics test scores for both years. While internet access at school does not improve the academic performance of students in 2007, it has a positive effect in 2009, although of smaller magnitude when compared to the effect of internet at home. The sensitivity analysis confirms the robustness of the results. The results along with previous research suggest that the efforts to increase internet access at schools can result in much higher magnitude of improvement of students' academic performance if they are combined with policy initiatives to increase home internet access and incorporate internet-based educational tools at schools.